Nikita Khrushchev : creation of a superpower - Khrushchev, Sergei (Pennsylvania State University Press, 2000)
More is known about Nikita Khrushchev than about many former Soviet leaders, partly because of his own efforts to communicate through speeches, interviews, and memoirs. (A partial version of his memoirs was published in three volumes in 1970, 1974, and 1990, and a complete version was published in Russia in 1999 and will appear in an English translation to be published by Penn State Press.) But even with the opening of party and state archives in 1991, as William Taubman points out in his Foreword, many questions remain unanswered. "How did Khrushchev manage not only to survive Stalin but to succeed him? What led him to denounce his former master [an event that some interpreters herald as the first act in the drama that led to the end of the USSR]? How could a man of minimal formal education direct the affairs of a vast intercontinental empire in the nuclear age? Why did Khrushchev's attempt to ease East-West tensions result in two of the worst crises of the Cold War in Berlin and Cuba? To resolve these and other contradictions, more than policy documents from archives and memoirs from associates are needed. We need firsthand testimony by family members who knew Khrushchev best, especially by his only surviving son, Sergei, in whom he often confided. As Sergei says, "During the Cold War, our nations lived on opposite sides of the Iron Curtain, and not only was it an Iron Curtain but it was also a mirror: one side perceived the other as the 'evil empire, ' and vice versa; so, too, each side feared the other would start a nuclear war. Neither side could understand the real reasons behind many decisions because Americans and Russians, representing different cultures, think differently. The result was a Cold War filled with misperceptions that could easily have led to tragedy, and we are lucky it never happened. And still, after the Cold War, American-Russian relations are based on many misunderstandings." In this book Sergei tells the story of how the Cold War happened in reality from the Russian side, not from the American side, and this is his most important contribution